A probable case of Actinomycosis (Lumpy jaw disease) withpseudo joint formation in dwarf cattle from the late medieval in Wysburg, Germany - Karl , Hans-Volker; Safi, Amtyaz (International Journal of Biological Research, 2024)
Actinomycetes are Gram-positive anaerobic bacteria that cause disease in cattle and sometimes other animals. Mandibular abscess is a localized, chronic, progressive granulomatous abscess that often involves the mandible, maxilla, or other bones of the head. When an infection occurs, byproducts of the infection begin to break down bones. This article aims to determine the possibility of disease in the medieval bones of these animals, to identify and analyze their macro-structural features and their diagnostic potential value in the archaeological skeletal material of studied animals. This late medieval (13th-14th century) document was found in Wysburg, near Weisbach in the Saale-Holzland-County in the central German state of Thuringia. Macroscopic and histopathological examination of the bone revealed a lesion in the lower jaw, suggesting that it may result from actinomycosis (Mostly in the jaw). Descriptions of jaw bones are rare in the paleo-pathological literature. Analysis is limited by the absence of other anatomical elements of the affected animals, which affects the interpretation of the paleo-pathological skeleton. For further research, it is recommended that similar studies be conducted on better-preserved animals.